Application of Problem-based Learning Model to Improve Students’ Problem-solving Skills of Class VII-E SMP Negeri 25 Malang - Hanifah, Sholihatin; Nengah Parta, I; Puspitasari, Lila (KnE Social Sciences, 2023)
The purpose of this study was to improve students’ mathematical problem-solving skills on the material of numbers through the problem-based learning model in class VII-E of SMP Negeri 25 Malang. Classroom action research (CAR) was applied in this study. The study was carried out on 28 students of class VII-E of SMP Negeri 25 Malang. This research was conducted in 2 cycles. Results from the first cycle of classical completeness tests of 64.29% increased to 85.71% in the second cycle. In the first cycle, the highest problem-solving aspect was obtained in the aspect of understanding the problem with a percentage of 83.93% and categorized as complete, while the lowest problem-solving aspect was obtained in the re-examining aspect with a percentage of 59.29% and categorized as incomplete. In the second cycle, the highest problem-solving aspect was obtained in the aspect of understanding the problem with a percentage of 92.86% and categorized as complete, while the lowest problem-solving aspect was obtained in the re-examining aspect with a percentage of 70.24% and categorized as incomplete. It is possible to say that students’ ability to solve mathematical problems had increased in the class VII-E of SMP Negeri 25 Malang during the academic year of 2022/2023, allowing the problem-based learning model to be used as an alternative method to improve students’ ability to solve mathematical problems. Keywords: problem-based learning, Kemampuan Pemecahan Masalah, Ketuntasan Klasikal